Change in Fibrosis 4 Index as Predictor of High Risk of Incident Hepatocellular Carcinoma After Eradication of Hepatitis C Virus. (5th February 2021) - Tamaki, Nobuharu; Kurosaki, Masayuki; Yasui, Yutaka; Mori, Nami; Tsuji, Keiji; Hasebe, Chitomi; Joko, Koji; Akahane, Takehiro; Furuta, Koichiro; Kobashi, Haruhiko; Kimura, Hiroyuki; Yagisawa, Hitoshi; et al.
Abstract: Background: It is unclear whether the fibrosis 4 index (FIB-4), a marker of liver fibrosis, at baseline and change in FIB-4 after sustained virological response (SVR) is associated with incident hepatocellular carcinoma (HCC) risk. In this study, we examined the association of incident HCC risk with baseline FIB-4 and sustained high FIB-4 (>3.25) at any time point after SVR. Methods: A total of 3823 patients who received direct-acting antiviral treatment and achieved SVR were enrolled. The FIB-4 was measured 24 weeks after the end of direct-acting antiviral treatment and achievement of SVR (SVR24), and 1, 2, and 3 years after SVR24, after which subsequent HCC development was investigated. Results: In patients with an FIB-4 >3.25 at SVR24 and 1, 2, and 3 years after SVR24, subsequent HCC development was significantly higher than in those with an FIB-4 ≤3.25 at each point. The rates of HCC development 1, 2, 3, and 4 years after SVR24 were significantly higher in patients with sustained FIB-4 >3.25 than in those whose FIB-4 decreased to ≤3.25 (5.4%, 9.2%, 11.7%, and 16.0%, respectively, vs 2.2%, 3.1%, 3.7%, and 4.4%; P  < .001). The adjusted hazard ratios (95% confidence intervals) for an FIB-4 >3.25 at SVR24 and 1, 2, and 3 years later were 3.38 (2.4–4.8), 2.95 (1.9–4.7), 2.62 (1.3–5.1), and 3.37 (1.4–9.8), respectively. Conclusions: The FIB-4 could be used to assess HCC development risk at any time after SVR, and changes in FIB-4 were associated with changes in the HCC development risk. Repeated assessments of FIB-4 could serve as a prognostic indicator of a high-risk HCC cohort that may require more intensive HCC surveillance strategy. Abstract : The fibrosis 4 index (FIB-4) at any time after sustained virological response and changes in FIB-4 were associated with hepatocellular carcinoma (HCC) risk. Repeated assessments of FIB-4 could help identify a high-risk HCC cohort that may require more intensive surveillance.